Ecological Flow Scheduling Solutions of Beijiang River - CHEN Yan; CHEN Xiang (Renmin Zhujiang)
Beijiang River is one of the four major river systems in the Pearl River Basin.The discharge of its control section Shijiao can represent the ecological flow of the Beijiang River.Additionally,it can also cooperate with the water regulation of Xijiang River during the saltwater intrusion in the Pearl River Delta and control the water volume of the Sixianjiao Section entering the delta,which is significant for the water security of Guangdong-Hong Kong-Macao Greater Bay Area.This paper first analyzes the current ecological flow of the control section of the Beijiang River.Then,the paper builds the reservoir group scheduling model according to the existing problems.Finally,it researches the ecological flow scheduling in the basin to propose an ecological flow scheduling scheme for the Beijiang River.